Impact of a tailored exercise regimen on physical capacity and plasma proteome profile in post-COVID-19 condition - Chowdhury, Mohammad Mobarak H.; Fontaine, Marie-Noelle; Lord, Sarah-Eve; Quenum, Akouavi Julite Irmine; Limoges, Marc-André; Rioux-Perreault, Christine; Lucier, Jean-François; Cliche, Dominic O.; Levesque, Dominique; Boisvert, François-Michel; Cantin, André M.; Allard-Chamard, Hugues; et al. (Frontiers in Physiology, 2024)
Individuals affected by the post-covid condition (PCC) show an increased fatigue as well as a variety of symptoms which negatively impact daily functioning. The goal of this study is to determine the impact of a closely monitored 8-week mixed exercise program on physical capacity and plasma proteomic profiles of PCC cases. PCC patients were randomly assigned to exercise and non-exercise groups. The supervised exercise program (3X/week) included 10-20 min of cardiovascular exercise and resistance exercises (all large muscle groups; 2-4/10 Borg scale 8-12 repetitions). Physical capacity and physical activity level were measured before and after the intervention. Plasma and peripheral blood mononuclear cell (PBMC) samples were collected at the beginning and end of the training program. Glutathione level in PBMC and plasma proteomic profiles were evaluated. Bicep Curl (+15% vs 4%; p=0.040) and Sit-to-Stand test (STS-30 (+31% vs +11%; p=0.043)) improved to a greater extent in the exercise group than in the nonexercise group. An interaction effect was also observed for the level of physical activity (p=0.007) with a positive effect of the program on daily activities without any adverse effects on general or post-effort fatigue. After exercise, glutathione levels in PBMCs increased in women but remained unchanged in men. Discernable changes were observed in the plasma proteomics profile with certain proteins involved in inflammatory response decreasing in the exercise group. Supervised exercise adapted to the level of fatigue and ability is safe and effective in PCC patients for improving some physical capacity to some extent without worsening fatigue or symptoms. Thus, systemic molecular markers that accompany physical improvement can be monitored by analyzing plasma proteomics and markers of oxidative stress.